Financial and Intellectual Conflicts of Interest Among Japanese Clinical Practice Guidelines Authors for Allergic Rhinitis. (17th August 2021) - Murayama, Anju; Kida, Futa; Ozaki, Akihiko; Saito, Hiroaki; Sawano, Toyoaki; Tanimoto, Tetsuya
Abstract : Objective: To elucidate financial and intellectual conflicts of interest (COIs) among clinical practice guideline (CPG) authors of allergic rhinitis in Japan and to evaluate the extent of transparency and accuracy in COIs by CPG authors of allergic rhinitis. Study Design: A cross‐sectional analysis of the payment data from all 79 pharmaceutical companies in Japan between 2016 and 2017. Setting: Japan. Methods: We considered all 27 CPG authors from 2 different versions of the most prominent CPGs for allergic rhinitis in Japan. Using payment data disclosed by 79 major pharmaceutical companies between 2016 and 2017, we assessed the magnitude and characteristics of financial COIs of CPG authors. We also evaluated the intellectual COIs of the CPG authors by counting self‐citations of research articles related to CPG statements and recommendations. Results: Of 27 CPG authors, 26 authors (96.3%) received at least 1 payment from a combined total of 1, 333, 552 between 2016 and 2017. The 2‐year combined average and median monetary values per author were 49, 391 (SD, 67, 438) and 18, 400 (interquartile range: 6, 216‐72, 494), respectively. Pharmaceutical companies with novel drugs predominantly made these payments. The percentage of citations with at least 1 CPG author relative to total citations was 47.6% in 2016 and 27.9% in 2020. There were no formal COI disclosure statements in either version. Conclusion: This study found that allergic rhinitis CPG authors had significant financial relationships with pharmaceutical companies, particularly those marketing novel drugs. In addition, CPG authors had relatively high self‐citation rates, a potential marker of intellectual COIs. More rigorous and comprehensive COI management strategies are needed.